Trends in adverse pregnancy outcomes in Louisiana, 2017 to 2022 - Chelsea L. Kracht; Emily W. Harville; Nicole L. Cohen; Elizabeth F. Sutton; Maryam Kebbe; Leanne M. Redman (Scientific Reports)
Abstract Natural disasters can lead to more adverse pregnancy outcomes (APO). It is unclear if the extended COVID-19 pandemic has impacted APOs and pre-existing conditions among perinatal populations with increased risk of severe maternal morbidity and mortality. A retrospective chart review was conducted of hospital records and birth certificates in the largest birth hospital in Louisiana from 2017 to 2022. Amongst 27,877 births (50.9% White, 38.3% Black, 28.9 ± 5.6 years), gestational diabetes (GDM) was lowest in pre-pandemic conceptions (11.0%, June 2017-May 2019) and rose to 16.4% early pandemic (October 2019-February 2020) but leveled off at 12.2% in peak (March 2020-February 2021) and late pandemic (March 2021-September 2021). Individuals who conceived in early and peak pandemic were 47% (95% CI 33, 63) and 11% (95% CI 2, 20) more likely to develop GDM respectively, compared to pre-pandemic conceptions. Individuals who delivered during early (aRR: 1.54, 95% CI 1.33–1.78), peak (aRR: 1.48, 95% CI 1.32–1.65), and late (aRR: 1.62, 95% CI 1.41, 1.85) pandemic were more likely to develop preeclampsia and HELLP syndrome compared to pre-pandemic conceptions. Individuals were also 17% (95% CI 5, 32) more likely to enter pregnancy with chronic hypertension in peak pandemic compared to pre-pandemic. In paired analysis (n = 3390), individuals with a pandemic conception that occurred early pandemic had a higher risk of developing GDM compared to their pre-pandemic pregnancy (aOR 3.26, 95% CI 1.52, 6.97). Supporting birthing individuals amongst significant stressful events, especially in early gestation, is critical for preventing APOs and severe maternal morbidity and mortality.